Community Forestry: a Viable Option for Forest Management - Jha, Suman Kumar; Hegde, Harsha; Thakur, N. S. (Indian Forester, 2011)
A major challenge for government agencies such as forest departments is to ensure that all staff members are well-trained and informed in the more technical areas of conservin managing and using forest genetic resources. Moreover, progress towards greater participation in forestry and conservation will require knowledge of participatory approaches and means of implementing them. It is crucial that staff members, who deal with local communities, are trained in these matters. Another challenge is to avoid bureaucratic bottlenecks that hinder problem solution and communication not only between officials and local communities, but also between different levels within bureaucracies. Community Forest Management has adopted different approaches to protect the regeneratinc forests and to regulate the extraction of forest products. The idea that the local communities can protect and manage forests has gained momentum in the present day. Traditionally, the village communities have used forests even though it had remained under the custoctY of the ruler. As a result of the growing scarcity of forest based needs efforts were made by the local communities to protect and regenerate degraded forests. With the increasing number of such instances of forest protection by village communities, the concept of community forest management has established itself as a strong alternative to the eartier forest management practices. Community forest management means involvement of local communities in the protection, management and conservation of forest resoun::es based on local expertise, knowledge and need. This implies a need based management system that has come to be known as a viable means to achieve sustainable forest management.